Testing of data‐centric and event‐based dynamic service compositions. (15th April 2013) - Hummer, Waldemar; Raz, Orna; Shehory, Onn; Leitner, Philipp; Dustdar, Schahram
SUMMARY: This paper addresses integration testing of data‐centric and event‐based dynamic service compositions. The compositions under test define abstract services that are replaced by concrete candidate services at runtime. Testing all possible instantiations of a composition leads to combinatorial explosion and is often infeasible. We consider data dependencies between services as potential points of failure and introduce the k‐node data flow test coverage metric, which helps to significantly reduce the number of test combinations. We formulate a combinatorial optimization problem for generating minimal sets of test cases. On the basis of this formalization, we present a mapping to the model of FoCuS, a coverage analysis tool. FoCuS efficiently computes near‐optimal solutions, which are used to automatically generate test instances. The proposed approach is applicable to various composition paradigms. We illustrate the end‐to‐end practicability based on an integrated scenario, which uses two diverse composition techniques: on the one hand, the Web Services Business Process Execution Language and on the other hand, WS‐Aggregation, a platform for event‐based service composition. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : This paper addresses the integration testing of data‐centric and event‐based dynamic service compositions, in which abstract services are replaced by concrete candidate services at runtime. We consider data dependencies between services as potential points of failure and introduce the k‐node data flow test coverage metric, which helps to significantly reduce the number of generated test combinations. We illustrate the end‐to‐end practicability based on an integrated scenario, which uses two diverse service composition techniques (Web Services Business Process Execution Language and WS‐Aggregation).